ANTHROPOLOGICAL SPHERE OF HUMAN EXISTENCE: RESTRICTIONS ON HUMAN RIGHTS DURING PANDEMIC THREATS - V. S. Blikhar; I. M. Zharovska (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The article is aimed to study the anthropological, socio-philosophical and philosophical-legal dimensions of the ontological sphere of human life within the discourse of restricting human rights during pandemic threats. To do this, one should solve a number of tasks, among which are the following: 1) to explore the anthropological and praxeological understanding of fear as a primary component of human existence in a pandemic, which prevents people from changing their lives for the better and healthier, having fun and happiness; 2) to put a focus on the habituation of fear as a two-dimensional (short-term and long-term) adaptation to risks and threats from pandemics; 3) to reflect the anthropological features of changes in human life experience under the influence of the COVID-19 pandemic in the discourse of human rights and public health measures. Theoretical basis. Today, international guiding principles on human rights response to global natural threats have been updated. However, there are still no specific legal recommendations (both at the international and national levels) concerning measures on human rights protection during outbreaks of various infectious diseases. However, the influence of unexpected global challenges (especially COVID-19 and not just that) causes a change in the anthropological component of society and the state, so it requires immediate comprehensive research. Originality. It was substantiated a systematic approach to the implementation of modern healthcare policy towards the recognition of human life as the highest value, increasing the level of psychological preparedness for pandemic challenges and approximation of statutory provisions of human rights protection to modern challenges and threats to the health of the individual, society and state. The study of anthropological, socio-philosophical and philosophical-legal dimensions of human existence in the discourse of pandemic threats made it possible to reveal the profound influence of fear on human life, social justice and, consequently, identify the moral and legal dependence of the development level of society and the state on the level of axiological and anthropological concept of human dignity. Conclusions. Based on the study of statistical reports, international analysis and the use of personal authorial methods, the following can be stated: the methods of combating the modern pandemic have directly affected everyone on national and international level. Their influence is significant because it changes the rules of coexistence and life of people in all spheres. However, the influence on the consciousness and other intentions of the individual has mostly temporally insignificant limits.